If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + 3) = 0 Reorder the terms: 3(3 + 3x) = 0 (3 * 3 + 3x * 3) = 0 (9 + 9x) = 0 Solving 9 + 9x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 9x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 9x = 0 + -9 9x = 0 + -9 Combine like terms: 0 + -9 = -9 9x = -9 Divide each side by '9'. x = -1 Simplifying x = -1
| 2xy/5x*10xy^3/22y/5y2z/11x^3 | | 15p=315 | | 36k^2-16k-20=0 | | -5p+-4(1-p)=3p+0(1-p) | | 12-5z/437 | | (-6x^9)(-9x^8)=1 | | Y-(-1)=3/4(x-6) | | 12-5z=37 | | 20f^2-56f+32=0 | | 25x=y+180 | | 3d^2-47d-16=0 | | 7x+12=-7x-17 | | 7+2x+2y=11 | | 5f=5+10 | | 6(3x-7)=-6 | | .75x-2=-7+.33x | | 3v^2-40v+13=0 | | 7x^2-4x+392=1904 | | 6j^2+35j-6=0 | | 7x=1.5 | | 4x^4+6x^3-17x^2-9x-5=0 | | 3p+8-6-3p= | | 3x^2-16=131 | | 11X+10=10X+10 | | 8x+4+40=180 | | N+3(n-1)=9 | | 10x+2=132 | | q^2+9q+7=0 | | g^2+3g-4=0 | | 8n=192 | | 2sin^2X=1-4cosx | | 4x^2+25x-15=0 |